Vitamin status in treated patients with cystic fibrosis. Issue 9 (September 1981) - Congden, P J; Bruce, G; Rothburn, M M; Clarke, P C; Littlewood, J M; Kelleher, J; Losowsky, M S
Abstract : The water-soluble (B1, B2, B6, C, folic acid) and fat-soluble vitamin (A, carotene, E, and D) status of 36 patients with cystic fibrosis was assessed and compared with a control group of 21 age-matched normal children. Twenty-seven of the patients were receiving vitamin supplements (except folic acid and vitamin E) at the time of investigation. Vitamin B1, B2, and B6 status was adequate in all patients, and there was little evidence of folic acid deficiency. Vitamin C stores might not have been adequate in some of these patients, despite daily supplements with 50 mg of the vitamin. Steatorrhoea, often severe, was present in most of them. Serum carotene and vitamin E concentrations were low in over 90% of patients and were related to the severity of steatorrhoea. Vitamin A was low in over 40% of the patients despite daily vitamin supplements of 4000 IU and correlated with the serum retinol-binding protein level. Serum 25-OH cholecalciferol was low in some patients whether or not they were receiving a daily supplement of 400 IU vitamin D. In a short-term supplementation trial with water-miscible preparations of vitamin A and E in 14 patients, the serum levels of both vitamins responded well to 2 weeks of treatment with 50 mg vitamin E and 4000 IU vitamin A. Except for serum vitamin A, which was lowest in patients with the poorest clinical grading, the other vitamins were not influenced by the clinical grade of the patients.